HOW DO CTHRC1 AND MATRIX METALLOPROTEINASES AFFECT PATHOLOGIC ACTIVITIES OF FIBROBLAST-LIKE SYNOVIOCYTES IN RHEUMATOID ARTHRITIS? - Kozhdan, Kamilya (Nazarbayev University School of Medicine, 2023)
Rheumatoid arthritis (RA) is an intricate autoimmune condition impacting approximately 1% of the global adult population. One of the key characteristics of this disease is the tendency of activated fibroblast-like synoviocytes (FLS) to invade and damage joint tissues. Recently, there has been a significant focus on discovering biomarkers that can precisely forecast the development of RA. One potential set of biomarkers includes collagen triple helix repeat-containing protein 1 (CTHRC1) and metalloproteinases (MMPs) proteins associated with migration and invasiveness of fibroblast-like synoviocytes, which are responsible for instigating inflammation and joint destruction in RA. The objective of this work is to investigate how CTHRC1 and MMPs are associated with the movement and invasive properties of FLS in the progression of RA. The study aims to assess whether the expression of these proteins can be used to anticipate the development of RA. The research will entail evaluating how CTHRC1 and MMP levels affect FLS pathogenesis. The conventional diagnostic markers for RA were used to show the correlation between potential biomarkers expression and disease activity. The results of this study could be significant for developing new targets for treatment and therapies for RA.
Keywords: type of access: gated access